2014
DOI: 10.3168/jds.2013-7708
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract size, total-tract digestibility, and rumen microflora in different dairy cow genotypes

Abstract: Interpretive Summary 67 DAIRY COW DIGESTIBILITY 68 3Beecher 69 70This study aimed to measure if differences existed among dairy cow genotypes in 71 gastrointestinal tract size, digestibility and selected rumen microbial populations. Jersey and 72JerseyHolstein-Friesian cows had proportionally larger gastrointestinal tract weight than 73Holstein-Friesian cows. Jersey cows had a superior total tract digestibility and lower relative 74 abundance of Ruminococcus flavefaciens in the rumen than Holstein-Friesian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 45 publications
11
46
0
Order By: Relevance
“…For example, Prendiville et al (2009) reported that Jersey (J) cows required 7 to 8% less total feed for every kilogram of milk fat and protein produced in a pasture-based dairy production system compared with HF cows. This is consistent with the reported differences in the mass of the gastrointestinal tract (i.e., 24% lighter in J cows; Beecher et al, 2014), a 2 to 3% greater digestibility of DM and NDF by J cows (Beecher et al, 2014), and the greater use of consumed ME for productive purposes by the J cow (L'Huillier et al, 1988) compared with HF cows. The improvement in the efficiency of ME use, however, was apparent only in a grazing environment with restricted DMI, where J cows produced 20% more milk/kg of DMI (L'Huillier et al, 1988); under ad libitum feeding, this ME conversion gain disappeared.…”
Section: Introductionsupporting
confidence: 86%
“…For example, Prendiville et al (2009) reported that Jersey (J) cows required 7 to 8% less total feed for every kilogram of milk fat and protein produced in a pasture-based dairy production system compared with HF cows. This is consistent with the reported differences in the mass of the gastrointestinal tract (i.e., 24% lighter in J cows; Beecher et al, 2014), a 2 to 3% greater digestibility of DM and NDF by J cows (Beecher et al, 2014), and the greater use of consumed ME for productive purposes by the J cow (L'Huillier et al, 1988) compared with HF cows. The improvement in the efficiency of ME use, however, was apparent only in a grazing environment with restricted DMI, where J cows produced 20% more milk/kg of DMI (L'Huillier et al, 1988); under ad libitum feeding, this ME conversion gain disappeared.…”
Section: Introductionsupporting
confidence: 86%
“…A study with dairy cattle failed to find a difference in microbial populations of high and low RFI cows (Rius et al, 2012). However, the relative abundance of Ruminococcus flavefaciens was correlated with digestibility and was considered a possible explanation for differences in efficiency of grazing Irish Jersey compared with Holstein cows (Beecher et al, 2014). In the end, it is difficult to know what is causal in the relationship between the microbiome and digestibility.…”
Section: Conversion Of Ge To Ne: Variation Among Cowsmentioning
confidence: 99%
“…It is well documented that improving productivity can lead to a reduction in CH 4 emissions per unit of produce (Chagunda et al, 2009;Wall et al, 2010;Cottle et al, 2011) while making mitigation strategies appealing to producers. Beecher et al (2014) and Palladino et al (2010) showed that Holstein-Friesian cows on perennial ryegrass silage diets offered at maintenance levels and grazing perennial ryegrass, respectively, may exhibit differences in production efficiency compared with Jersey and Jersey × Holstein-Friesian cows. However, comparisons of CH 4 emissions between Holstein and other breeds under grazing or zero-grazing conditions have been limited, with the literature focusing on ensiled forage (Xue et al, 2011;Arndt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%